2012
DOI: 10.1007/s10546-012-9718-5
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Turbulence Structures and Their Contributions to the Momentum Flux and Turbulence in the Near-Neutral Atmospheric Boundary Layer Observed from a 213-m Tall Meteorological Tower

Abstract: Large-scale turbulence structures in the near-neutral atmospheric boundary layer (ABL) are investigated on the basis of observations made from the 213-m tall meteorological tower at Tsukuba, Japan. Vertical profiles of wind speed and turbulent fluxes in the ABL were obtained with sonic anemometer-thermometers at six levels of the tower. From the archived data, 31 near-neutral cases are selected for the analysis of turbulence structures. For the typical case, event detection by the integral wavelet transform wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…On the other hand, Helgason and Pomeroy (2012) relate these low-frequency contributions to the gustiness of the flow. Horiguchi et al (2012) also report the active role of intermittency in the spatio-temporal evolution of these large-scale, coherent structures. Additionally, Dupont et al (2008) and Horiguchi et al (2012) also observed an elevated maximum in the momentum flux (their Figs.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…On the other hand, Helgason and Pomeroy (2012) relate these low-frequency contributions to the gustiness of the flow. Horiguchi et al (2012) also report the active role of intermittency in the spatio-temporal evolution of these large-scale, coherent structures. Additionally, Dupont et al (2008) and Horiguchi et al (2012) also observed an elevated maximum in the momentum flux (their Figs.…”
Section: Discussionmentioning
confidence: 77%
“…Horiguchi et al (2012) also report the active role of intermittency in the spatio-temporal evolution of these large-scale, coherent structures. Additionally, Dupont et al (2008) and Horiguchi et al (2012) also observed an elevated maximum in the momentum flux (their Figs. 7 and 8, respectively), similar to that found at Pometeno Brdo.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Instrumented towers have been used widely around the world to study the surface layer and lower portion of the boundary layer [e.g., Van Ulden and Wieringa , ; Whiteman et al ., ; Bowen , ; Horiguchi et al ., ; Munoz et al ., ; Sorbjan and Czerwinska , ]. In addition to these midlatitude surface layer studies, instrumented towers have been used to analyze the surface layer in the polar regions, where snow and ice covered surfaces greatly influence the stability of the near‐surface atmosphere [e.g., Riordan , ; Persson et al ., ; Grachev et al ., ; Hudson and Brandt , ; Genthon et al ., ; Grachev et al ., ; Genthon et al ., ; Grachev et al ., ; Van dam et al ., ].…”
Section: Introductionmentioning
confidence: 98%
“…A meteorological observation tower provides a representative way to continuously measure vertical profiles of atmospheric variables at the site of interest for a long period. Several tall meteorological towers with heights of a few hundred meters have been installed in Boulder, USA [15], Tsukuba, Japan [16], Beijing, China [17], Boseong, South Korea [18], and Shenzhen, China [19], and have been used to observe the temporal evolution of the vertical profiles of various meteorological variables in the lower ABL. A meteorological observation tower is the most accurate in situ arrangement for obtaining meteorological data at various altitudes.…”
Section: Introductionmentioning
confidence: 99%